Determinanty komunikacji w zarządzaniu projektem na przykładzie projektu "Podnoszenie kwalifikacji językowych osób pracujących w województwie lubuskim" - Wysocki, Robert (Theoretical and Practical Communication Aspects in Project Management - Based on the Project : "The Improvement of Language Qualifications Among Working People in the Lubuskie Province", 2008)
The paper addresses selected issues involved in the process of communication within a project, on the example of the "Raising language competence of employees of Lubin region" project, co-funcled by the European Social Fund and state budget. Based on theoretical assumptions, the paper analyses functions of the so-called information wall, i.e. project webpage being part of an authored ICT solution supporting project management. Benefits and dangers of the information wall are shown, taking into account project characteristics, such as range, time frame, area of influence and list of beneficiaries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 166-179